Clinical nursing skills : core and advanced - Cooper, Simon , 1967-; Endacott, Ruth; Jevon, Phil (Oxford University Press, 2009)
Designed as a compelling text for students, 'Clinical Nursing Skills' offers evidence-based, practical guidance for procedures in all settings. Emphasis is placed on the development of decision-making and problem-solving skills